IMPLEMENTASI SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT TULANG PADA MANUSIA MENGGUNAKAN METODE FORWARD CHAINING - Ferly Ardhy; Romadon Romadon; Neli Oktaliasari (STMIK Dian Cipta Cendikia Kotabumi, 2019)
Bone disease is a condition that damages the skeleton and makes bones weak and vulnerable to fractures. The high disease is caused by ignorance and lack of knowledge about the disease. Therefore, an expert system was created to diagnose bone disease in humans. The method used in making this expert system is the forward chaining method, forward chaining method using the PHP programming language and MySQL database. The results of this study are the application of expert systems to diagnose human bone disease using a forward chaining method that can be accessed by the public at large to diagnose early symptoms of bone disease without limited distance and time used.